Validated Spectrophotometric Estimation of Famciclovir in Tablet Dosage Form - J. Adlin Jino Nesalin; C. Jose Gnana Babu; G. Vijaya Kumar; T. Tamizh Mani (E-Journal of Chemistry)
Two simple and sensitive spectrophotometric methods have been developed for the estimation of Famciclovir (FCR) in bulk and tablet dosage form. Methods A and B are based on the formation of ion-pair complexes of the drug with dyes such as orange II (OG-II) and alizarin red S (AR-S) in acidic medium followed by their extraction with chloroform to give colored chromogen with absorption maxima at 480 nm and 440 nm respectively. Beer’s law is valid in the concentration range of 2-10 mcg/mL for both the methods. These developed methods were validated for precision, accuracy, ruggedness and robustness. Statistical analysis proves that the methods are reproducible and selective for the routine analysis of the said drug.